2016
DOI: 10.1007/s11695-016-2185-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bioavailable Vitamin D Concentrations and Bone Mineral Density in Women After Obesity Surgery

Abstract: Serum bioavailable 25-hydroxyvitamin D concentrations are not associated with bone mass loss after bariatric surgery in women. The negative association with serum PTH levels suggests that vitamin D supplementation partly improves secondary hyperparathyroidism, yet other mechanisms may contribute to low bone mass after bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
3
0
1
Order By: Relevance
“…19 Several studies have conducted across the world and observed that Vit-D status can influence the progression of MS. In a study conducted by Botella-Carretero JI et al, found that Vit-D status is associated with MS among the obese population in U.S. 20 Some of the major factors observed in our study are the considerable abnormalities in lipid profiles. In our study, the Vit-D deficient group had high LDL-C and reduced the HDL-C level.…”
Section: Discussionsupporting
confidence: 51%
“…19 Several studies have conducted across the world and observed that Vit-D status can influence the progression of MS. In a study conducted by Botella-Carretero JI et al, found that Vit-D status is associated with MS among the obese population in U.S. 20 Some of the major factors observed in our study are the considerable abnormalities in lipid profiles. In our study, the Vit-D deficient group had high LDL-C and reduced the HDL-C level.…”
Section: Discussionsupporting
confidence: 51%
“…Although these hormonal changes are thought to impart many of the positive metabolic benefits of bariatric surgery, they may also contribute to bone loss. Hence, it remains essential to monitor levels of calcium, vitamin D, and parathyroid hormone both before and in the long term after bariatric surgery [18][19][20][21][22].…”
Section: Bone Loss After Bariatric Surgerymentioning
confidence: 99%
“…In addition, rates of secondary hyperparathyroidism are high in post-RYGB patients (23.7%-42%), although lower than in post-BPD-DS patients (72.5%). Furthermore, secondary hyperparathyroidism may develop in patients despite normal circulating levels of calcium and vitamin D, so other factors, such as calcium malabsorption, age, and menopausal status, may play a role [18,28,29]. Another contributing factor is decreased mechanical loading related to weight loss after RYGB, given that mechanical loading under normal circumstances is the principal mechanism in maintaining bone mass, strength, and size.…”
Section: Gastric Bypassmentioning
confidence: 99%
“…References of the studies reviewed in this section: [ 7 , 10 , 11 , 12 , 13 , 14 , 16 , 17 , 18 , 20 , 21 , 22 , 25 , 26 , 28 , 30 , 31 , 32 , 35 , 36 , 37 , 38 , 39 , 42 , 43 , 44 , 45 , 50 , 51 , 52 , 57 , 62 , 65 , 67 , 71 , 72 , 73 , 74 , 75 , 77 , 80 , 81 , 82 , 83 , 84 , 85 , 87 , 89 , 90 , 93 , 95 , 96 , 97 ,…”
Section: Discussionunclassified